Probiotics in Pediatric Atopic Dermatitis: Prevention and Therapeutic Potential – A Literature Review - Kamińska, Zuzanna Zofia; Zielińska, Agnieszka; Mrozek, Martyna; Blecharczyk, Małgorzata; Zydlewski, Igor; Malcher, Aleksandra; Pacanowska-Trawnicka, Martyna; Jakimowicz, Aleksandra (Quality in Sport, 2026)
Introduction. Atopic dermatitis (AD) is a chronic inflammatory skin disorder characterised by impaired epidermal barrier and immune dysregulation. It is becoming increasingly prevalent in the pediatric population. Recent research highlights the role of the gut-skin axis and suggests that the intestinal microbiota may influence the development and course of inflammatory skin diseases, including AD. Aim of the study. This review aims to evaluate the current evidence regarding the use of probiotics in the treatment and prevention of atopic dermatitis in the pediatric population. Material and methods. A literature search was conducted using the PubMed database to identify relevant studies discussing the role of probiotics in treatment and prevention of atopic dermatitis in children. Meta-analyses, randomized controlled trials and systematic reviews were included. Results. Included studies suggest that probiotic supplementation may reduce the severity of atopic dermatitis, as measured by the SCORAD index, particularly in moderate-to-severe AD, and when administered for longer durations. Moreover, they may be useful in prevention of AD in high-risk infants, especially during the prenatal period. However, results vary depending on study design, probiotic strain, population and duration of supplementation. Conclusion. Probiotics may be a promising new strategy as an adjunct therapy in the treatment and prevention of pediatric atopic dermatitis. Nevertheless, further research, mostly well-designed randomized controlled trials are needed in order to determine optimal strains, dosage and duration of treatment.